2012
DOI: 10.1371/journal.pone.0048800
|View full text |Cite
|
Sign up to set email alerts
|

Five Cryptic Species in the Amazonian Catfish Centromochlus existimatus Identified Based on Biogeographic Predictions and Genetic Data

Abstract: Accurately quantifying biodiversity is fundamental for both evolutionary theory and conservation strategies. DNA-based studies are exposing high cryptic diversity irrespective of taxonomic group or environmental setting, and increasing the ever-growing estimates of global biodiversity. This has severe implications for under-sampled and species-rich tropical regions, such as the Amazon Basin. We used biogeographic predictions derived from geomorphological history and contemporary hydrochemical and genetic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…11). Similar biogeographical patterns and speciation events associated with the Pebas system and marine incursions in the Middle and Late Miocene have been reported for several groups in the Amazon region (Hoorn 1993, Lovejoy et al 1998, 2006, Lundberg et al 1998, Wesselingh 2006, Santos et al 2009, Cooke et al 2012a,b). Therefore, the proposed current parapatric distribution of the “carteri” and “ivonicus/yuna” lineages probably developed after the establishment of the modern west-to-east course of the Amazon River, which may have initiated approximately 8 Ma (Lundberg et al 1998).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…11). Similar biogeographical patterns and speciation events associated with the Pebas system and marine incursions in the Middle and Late Miocene have been reported for several groups in the Amazon region (Hoorn 1993, Lovejoy et al 1998, 2006, Lundberg et al 1998, Wesselingh 2006, Santos et al 2009, Cooke et al 2012a,b). Therefore, the proposed current parapatric distribution of the “carteri” and “ivonicus/yuna” lineages probably developed after the establishment of the modern west-to-east course of the Amazon River, which may have initiated approximately 8 Ma (Lundberg et al 1998).…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, a morphometric study with specimens from the Negro River revealed that they form a morphometrically distinct group from populations that inhabit white water, although some overlapping was found (García-Dávila et al 2005). Studies with fishes reported a similar pattern, providing evidence for the effect of divergent natural selection associated with the difference in water colour between the Negro River and Solimões-Amazon River (Cooke et al 2012a,b). Genetic divergence between hydrologically different, but interconnected, environments has been reported for other palaemonid species without a conspicuous and consistent morphological differentiation (Carvalho et al 2013).…”
Section: Discussionmentioning
confidence: 72%
“…Although the Amazon Basin sustains the world's richest freshwater fish fauna (Reis et al ), the growing number of cryptic species of Amazonian fish detected with molecular techniques (Littmann et al ; Nakayama et al ; Hubert et al ; dos Santos Silva et al ; Sistrom et al ; Nagamachi et al ; Piggot et al ; Cooke et al ) suggests that species richness in this group is vastly underestimated. A recent comprehensive assessment of cryptic diversity in Amazonian frogs also pointed to a similar conclusion (Funk et al ).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that water colour gradients structure Amazonian fish assemblages via the adaptive divergence of fishes to water colours, ultimately leading to ecological speciation events (Beheregaray, Cooke, Chao, & Landguth, 2015;Cooke, Chao, & Beheregaray, 2012a, 2012b, 2012c, 2012dCooke, Landguth, & Beheregaray, 2014). Ecological gradients and ecotones are commonly known to generate biodiversity via divergent natural selection (Endler, 1973;Smith, Schneider, & Holder, 2001;Smith, Wayne, Girman, & Bruford, 1997).…”
Section: Domingosmentioning
confidence: 99%